EXPLORING ENGLISH TEACHERS’ STRATEGIES IN COPING WITH STUDENTS’ MISBEHAVIOR IN LEARNING ENGLISH: A CASE STUDY AT A PRIVATE VOCATIONAL HIGH SCHOOL IN PEKANBARU - Hemniati Hemniati; Abdul Hadi; Promadi Promadi (Lembaga penelitian dan pengabdian kepada masyrakat, 2021)
This research aims to exploring English teachers’ strategies in coping with students’ misbehavior in learning English at a Private Vocational High School Pekanbaru. The study employed qualitative approach. The participants of this study involves two English teachers and 85 students of ten grade class. The data collecting technique used in this study were observation and interview. The result of this research discover six types of teachers’ strategies used by English teacher in coping with students’ misbehavior in the classroom. They were; (1) Verbal strategies, (2) Reprimand and punishment, (3) Non-verbal strategies, (4) Pre-empting misbehavior, (5) Dealing with confrontation, and (6) Pastoral care. Verbal strategies and reprimand and punishment used by English teacher quiet often in the classroom. However, verbal strategies is the most frequently strategies used by English teachers in coping with students’ misbehavior in English lessons at SMK TARUNA SATRIA Pekanbaru.